THE EXPERIENCE OF INDONESIAN NURSES HANDLING EMERGENCY CONDITION IN OVERSEAS ARMED CONFLICT - Desi Susilawati; Retty Ratnawati; Fransiska Imavike Fevriasanty (Journal of Nursing Science Update (JNSU), 2019)
Handling victim of armed conflict area would need involvement from all stakeholders, including nurses. To run his role in conflict incident, nurse would have to deal with lots of complex problems and demands. Knowing nurse’s experience in handling victim at armed conflict area can become the basic to improve service toward victim. The purpose of this research is to explore Indonesian nurse’s experience in giving emergency treatment toward victim of armed conflict areas overseas. Qualitative study design with interpretive phenomenology approach and involving 7 Indonesian nurses who were involved in handling victim at armed conflict areas overseas. Data collected through in depth interview and analyzed using Braun & Clarke thematic analysis. This study resulted 12 theme, calling from the heart, have an adventurous soul when faced the reality, diversity in preparation before departure, faced the unpredictable condition, take a modified action and human resources, dilemma when delivering the health service in restricted area, anxiety but tried to be professional. Using defensive strategy in security limitations and threats, feeling satisfied because delivering the health service beyond their standard. Expecting th improvement in preparation cooperation with related organization. Giving treatment toward victim at armed conflict area overseas is a complex and has many challenges. Strong motivation, perfect preparation and good adaptation skill would highly needed to be able to give maximum handling toward victim. There should be improvement in and improvement in cooperation with related parties in order to give maximum treatment.